Application of Agile Methodology in Managing the Healthcare Sector - Alotaibi, Fawaz; Almudhi , Riyad (iRASD Journal of Management, 2023)
The healthcare sector has gradually embraced effective project management for improved healthcare outcomes. This paper explores the application of the agile methodology for managing the healthcare sector. This study significantly contributes to the healthcare sector by providing insights into the application of Agile methodology, potentially enhancing healthcare management and patient outcomes. In this article, the author reviews ten peer-reviewed articles, analyses the findings, and generates three themes: Agile methodology development and implementation in the healthcare sector, the healthcare sector's readiness factors/levels for applying the agile methodology, and how agile methods improve healthcare outcomes. The findings across the three identified themes reiterate the crucial role of organizational leadership, flexible structures, and advanced technology in enhancing agility within the healthcare sector. Moreover, the studies highlight the potential of agile principles to enhance customer-centricity, customer satisfaction, and overall adaptability in healthcare organizations. The study recommends healthcare institutions priorities Agile competency development through training programs and cultivate a culture of adaptability to support Agile methodology adoption. Furthermore, it suggests quantitative research to validate readiness factors' influence, focusing on patient-centered outcomes and comparative studies between Agile and traditional healthcare approaches to bridge literature gaps.